Surface homogenizing heterostructure coatings induced by Ti3C2Tx MXene for enhanced cycle performance of lithium‐rich cathode materials. (19th February 2020) - Liu, Yanying; Li, Jianling; Yu, Yang; Huo, Xiaogeng; Zhong, Jianjian; Yang, Zhe; Li, Ranran
Summary: The layered lithium‐rich manganese‐based cathode material (Li1.2 Mn0.54 Co0.13 Ni0.13 ) has the significant advantage of high specific capacity, but this material also suffers serious defects, including severe capacity attenuation and voltage attenuation during the cycle. At present, most researchers have been working to optimize the cycle performance of lithium‐rich materials. In this work, we propose a surface homogenizing heterostructure coating induced by MXene modification to reduce capacity reduction and voltage decay. It can be found that the initial Coulombic efficiency (ICE) increases from 77.2% for the bare electrode Li1.2 Mn0.54 Co0.13 Ni0.13 (LMO) to 85.5% for 1.4 wt% MXene (Ti3 C2 Tx, Tx represents the surface terminations: OH, O, F) modified lithium‐rich (TO2). Furthermore, the discharge specific capacity of the electrode at 5 C rate increased from 160.7 mAh g −1 for LMO to 200.6 mAh g −1 for TO2. More prominently, the outstanding cycle stability with capacity retention rate is 82.1% for TO2 after 200 cycles, while only 64.7% for LMO, and the average discharge voltage dropped from 0.788 to 0.468 V. In addition, the mechanism for improving the electrochemical performance is systematically studied. Abstract : The figure is a schematic diagram of the formation process of the surface functionalized heterostructure coating. It is worth noting that the coating is thin and uniform, and a large number of spinel phase can be clearly found on the electrode surface by TEM analysis.